ANALISIS PLATFORM SP4N LAPOR! DALAM PERANNYA MENDORONG KETERBUKAAN INFORMASI PUBLIK - Athaya Aurelia Bilqis; Natasya Aliputri; Rizqa Aisyah Andini; Shella Andini Dwi Lestari (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This writing aims to conduct an analysis of the SP4N LAPOR! in encouraging openness of public information in society. The main focus of the research is to see how the implementation of SP4N LAPOR! made by the government, can be said to be effective for society. This author will explain advances in technology and communication for the public in accessing digital platforms. The research method was carried out qualitatively by collecting and analyzing data through literature study. The results of the discussion show the effectiveness of the SP4N LAPOR! regarding public complaints has not been fully implemented optimally, in its implementation there are still several shortcomings, such as a lack of good coordination between government institutions, and a lack of public socialization of the SP4N LAPOR! thus giving rise to a lack of public awareness regarding public information, and responses that are too normative. Apart from the effectiveness aspect, this article will also discuss the obstacles faced by the government and society in using the SP4N LAPOR! related to public information disclosure. Therefore, the aim of the SP4N Platform LAPOR! is an interactive medium between government and society, by encouraging active involvement in evaluating public service performance.